Research on the American defense acquisition procedures and its evolution based on engineering theory - WANG Wenping; CAO Yi; XIA Min; ZHENG Dangdang (Hangkong gongcheng jinzhan)
Through the introduction of 5000 series Defense Acquisition Procedures and it's evolution and development process of the U.S. Department of Defense，combined with the review of the defense acquisition outcomes in general and the development of typical major defense acquisition programs，and according to the engineering theories such as systematology，Philosophy of engineering，theory of engineering knowledge，the characteristics of complexity，knowledgeability，systematicness and integration of major defense acquisition program are explored in this paper. The reasons for the evolution，development of the defense acquisition procedures in the United States are analyzed. The strategy of applying knowledge-based approach to deal with risks in defense acquisition is introduced and the in-depth application is promoted. Some perspectives which may be useful for reference and reflection are put forward.